Pekan Sehat Remaja Dan Pemuda Pemudi Dusun Wonorejo, Sariharjo, Ngaglik, Sleman - Farida Noor Irfani; Yuyun Nailufar (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Non-Communicable Diseases (PTM) are chronic diseases with a long duration with a generally slow healing process or control of clinical conditions. Unhealthy lifestyles such as uncontrolled diet, lack of physical activity, and smoking habits contribute to the increase in the prevalence of NCDs worldwide. Diabetes mellitus is a type of PTM that now infects many people starting from their teenage years. Therefore, this community service was carried out as an initial screening effort related to the health condition of adolescents and young people in Wonorejo hamlet through a series of basic examinations including measurements of height and weight, blood pressure, blood glucose levels at the time, uric acid levels, and blood group tests. Most of the health examinations of adolescents and young people show results within the normal range. This results that the health condition of ORMAMI members is healthy and in the same. This activity is important to be carried out continuously as a preventive measure against various types of diseases.